2018
DOI: 10.29392/joghr.2.e2018039
|View full text |Cite
|
Sign up to set email alerts
|

Pilot peer health education for noncommunicable disease prevention in Bangladesh, Ethiopia, and Palau

Abstract: Back Background groundNoncommunicable diseases (NCDs) are growing health threats in developing countries. We previously conducted epidemiological and qualitative ethnographic studies on NCD risk factors in Bangladesh, Ethiopia, and Palau, and found that NCD risk factors were significantly prevalent. Although people had some knowledge of NCDs, they had no clue to change their daily risky behaviour, revealing urgent needs for developing appropriate health education programs. Peer health education is a strategy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“… 56 , 57 Furthermore, education and training at the interpersonal level are essential for improving the intrinsic abilities of a person to avoid health-risk behaviors. 59 On the other way, a pilot study on peer health education for NCD prevention in Bangladesh, Ethiopia, and Palau showed that peer health education is an effective strategy for preventing NCDs in resource-limited settings; 60 however, in this study, the method was not common in dealing with NCDs.…”
Section: Discussionmentioning
confidence: 66%
“… 56 , 57 Furthermore, education and training at the interpersonal level are essential for improving the intrinsic abilities of a person to avoid health-risk behaviors. 59 On the other way, a pilot study on peer health education for NCD prevention in Bangladesh, Ethiopia, and Palau showed that peer health education is an effective strategy for preventing NCDs in resource-limited settings; 60 however, in this study, the method was not common in dealing with NCDs.…”
Section: Discussionmentioning
confidence: 66%
“…The findings of the current study could be a basis for hypertension control programmes in northern Ethiopia, which we piloted previously. 38 The limitation of this study is that due to the nature of a cross-sectional study, causal relationships could not be identified. Another limitation is that there might be interobserver errors in measuring waist circumference and hip circumference.…”
Section: Discussionmentioning
confidence: 94%
“…As proposed by De Rosis et al [ 78 ], when designing health promotion initiatives following the peer-to-peer approach, the groups of adolescents characterized by healthy behaviors could be trained, activated, and engaged as positive testimonials and facilitators of positive lifestyles towards their peers, thus promoting healthier communities. Nevertheless, peer-to-peer initiatives are not a priori successful [ 109 , 110 , 111 , 112 ]. To this respect, it is worth pointing out that the findings of this DCE clearly highlight that, in general, adolescents do not prefer alternatives of travel that encompass friends, neither parents.…”
Section: Discussionmentioning
confidence: 99%